Identification of a Novel Hb H Disease with Glucose-6-Phosphate Dehydrogenase Deficiency Using Whole Genome Sequencing. (4th May 2022) - Ren, Zhen-Min; Xing, Zhi-Hao; Chen, Shi-Lin; Fu, Xiao-Ying; Chen, Yun-Sheng; Li, De-Fa
Abstract: With the development of sequencing technology, more and more rare thalassemia types have been found. In this article, we found a novel Hb H disease combined with glucose-6-phosphate dehydrogenase (G6PD) deficiency through whole genome sequencing (WGS), which was verified by Sanger sequencing and polymerase chain reaction (PCR)-reverse dot-blot hybridization, respectively.